Practical tips for conducting gender-responsive data collection - Elias, Marlène; Bioversity International (2013)
This two-page publication provides practical tips for carrying out gender-responsive data collection. The issues covered include paying attention to the composition of the field team, collecting gender-disaggregated data, examining how gender intersects with other forms of social difference, seeking appropriate approvals, scheduling activities at appropriate times and places, seeking privacy, using appropriate language, managing group dynamics and feeding back findings to participants in gender-responsive ways.